Kincraft : The Making of Black Evangelical Sociality - Thomas, Todne (Book collections on Project MUSE., 2021)
"In Kincraft: The Making of Black Evangelical Sociality Todne Thomas explores the interiority of black evangelical community life-a religious constituency often overshadowed by a white evangelical majority and the common equation of the "black Church" with an Afro-Protestant mainline. Informed by her fieldwork in an Afro-Caribbean and African American church association in the Atlanta metropolitan area, Thomas argues that church members co-create themselves as spiritual kin through the conceptual and performative labor of kincraft. Thomas attributes this kincraft-church members' constructions of one another as "brothers and sisters in Christ," "spiritual mothers," "spiritual fathers," "spiritual children,"and "prayer partners"-to religious and diasporic influences"--